The Environmental Problem As a Priority for Political Theorizing - Pegah Mossleh (رهیافتهای سیاسی و بین المللی)
The number of political thinkers who find themselves facing the environmental problems and realize that it is necessary to pay attention to this issue in contemporary political theory is gradually increasing. The problematic nature of the issue is now appeared in two interrelated features in political theorizing. First, in understanding the political factors that create micro and macro environmental problems, and second, in understanding how to deal with them politically. Political theory, as constructive framework of political processes, institutions and actions based on political concepts and value, raises the question of what measures can be taken to prioritize environmental problematics in power relations. In other words, for the political theorist this question arises that how power relations should be "directed", according to a particular political philosophy, in such a way that environmental concerns would be always considered as a fixed priority in these relations. This article is the result of reflection and research with an analytical-critical method on aspects of the environmental problem which require appropriate political theorizing to solve.